The measure of quality education - Abd Razak, Dzulkifli (2010)
I was browsing through Forbes (July 17) when the headline Ranking the US Celebrity 100 caught my attention. Given the craze to rank all things (the latest being "quality of death" where Malaysia is no. 33 out of 40 countries according to The Economist, July 17), I was curious to read about the ranking of celebrities.